Development of a calculation model and production cost index for feedlot beef cattle - Sartorello, Gustavo Lineu; Sigolo Teixeira Bastos, Joao Paulo [UNESP]; Gameiro, Augusto Hauber (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2018)
The objective of this study was to develop a feedlot beef cattle calculation model and production cost analysis and, from the results obtained, devise a production cost index. A case study was conducted to understand the characteristics of the productive processes of a commercial feedlot. Then, based on the Economic Theory, cost items of the farm under analysis were identified and transferred to a spreadsheet. The survey included ten feedlot farmers from the state of Sao Paulo and other nine from the state of Goias and was carried out to determine representative properties, and prices of items used were monitored. Production costs of each farm were calculated, and theoretical concepts of index numbers were used to devise the feedlot cattle production cost index. The cost allocation scheme was divided into four cost groups: variable, semi-fixed, fixed, and production remuneration factors. The developed model allowed a cost prognosis of the analyzed systems. Highest total costs for Sao Paulo State feedlots were R$ 9.17 kg(-1) and R$ 9.08 kg(-1) for average-sized and large farms, respectively, as contrasted to that of Goias, of R$ 8.29 kg(-1). Between the months April and June, the cost of production for feedlot beef cattle showed reductions of 1.48 and 1.40% for the average and large feedlots in the State of Sao Paulo and 9.13% for the Goias feedlot by the Konus Exact Index, respectively. Studies available in literature were compared and it was concluded that the model can help feedlot cattle farmers take production decisions. The Konus Index allows for a methodological advancement in relation to other studies carried out on the Brazilian livestock industry; besides, it can contribute to the sector organization.
Keywords: economic indicators; economy; livestock; mathematical model; production systems; survey